EFFECTS OF THE INQUIRY MATHEMATICS LEARNING (5E) THROUGH REAL LIFE SITUATIONS ON MATHEMATICAL REASONING BASED ON THE PISA ASSESSMENT FRAMEWORK - Pheaukkhai, Chayapha; Cheausuwantavee, Chommanad; Yamrung, Rungtiwa (Journal of MCU Nakhondhat, 2023)
The purposes of this study are as follows: 1) to compare students’ mathematical reasoning based on the PISA assessment framework before and after administrating the inquiry mathematics learning (5E) through real life situations; 2) to compare students’ mathematical reasoning based on the PISA assessment framework of students after administrating the inquiry mathematics learning (5E) through real life situations with the criterion of 70%. The sample of this study included 38 Matthayomsuksa Four students in the second semester of the 2022 academic year at Srinakharinwirot University Prasarnmit Demonstration School (Secondary). They were selected using the cluster random sampling technique. The duration of the research was 16 periods. The instruments used in this study were lesson plans and mathematical reasoning based on the PISA assessment framework test, an item of objective congruence of 0.67-1.00, difficulty of 0.25 – 0.75, an item discrimination of 0.20 – 0.90 and a reliability of 0.79. This research used the One Group Pretest-Posttest Design. The statistical procedures used for data analysis were a t-test for dependent samples and a t-test for one sample. The results revealed the following: 1) the mathematical reasoning based on the PISA assessment framework of the students after experiencing the inquiry mathematics learning (5E) through real life situations were higher than before and at a statistically significant level of .05; and 2) the mathematical reasoning based on the PISA assessment framework of the students after experiencing the inquiry mathematics learning (5E) through real life situations was higher than the criterion of 70%, with a statistically significant level of .05 and an average of 23.45, amounting to 73.28%.